Investigating factors influencing non-use and abandonment of microblogging services - Guo, Y.; Goh, D.H.-L.; Ilangovan, K.; Jiao, S.; Yang, X. (Journal of Digital Information Management, 2012)
This study explores the reason for non-usage and abandonment of microblogging. While previous studies mainly focused on individual behaviors associated with the use of social media, this research identifies why people do not use, or terminate their microblogging accounts. Studying the reasons for non-usage and abandonment is important as it helps organizations devise strategies to counteract this behavior by addressing nonusers' concerns. First, focus group interviews were conducted to uncover non-usage reasons. The elicited reasons were then used to construct a survey instrument and administered. Our results suggests that preference for other technologies, privacy concern and time constraints are the top three reasons contributing to the non-use and abandonment of microblogging accounts. The paper also proposes potential improvements to microblogs to attract more users.
Keywords: Abandonment; Focus Group; Microblogging; Non-use; Social media; Social networks; Survey